2013
DOI: 10.1093/aje/kws364
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study of Restless Legs Syndrome and Risk of Erectile Dysfunction

Abstract: In our previous cross-sectional study, we found that restless legs syndrome (RLS) was associated with erectile dysfunction (ED). Thus, we conducted a prospective study to examine whether RLS was associated with a higher risk of developing ED based on 6 years of follow-up among 10,394 men (mean age = 63.4 years) in the Health Professionals Follow-up Study. RLS was assessed in 2002 using a set of standardized questions recommended by the International RLS Study Group. Erectile function was assessed by means of q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…Second, since we only ascertained ED via a single self-reported questionnaire on ED onset during approximately 7 years after blood draw, we cannot exclude the recall bias as a possible explanation of our results. Furthermore, our assessment of ED has not been validated; however, we note that a prior report using these data [ 22 ] were consistent with what has been found in other studies [ 15 , 23 ]. Nonetheless, these two methodological weaknesses regarding the ascertainment of ED may lead to misclassification between incident ED and healthy controls.…”
Section: Resultssupporting
confidence: 86%
“…Second, since we only ascertained ED via a single self-reported questionnaire on ED onset during approximately 7 years after blood draw, we cannot exclude the recall bias as a possible explanation of our results. Furthermore, our assessment of ED has not been validated; however, we note that a prior report using these data [ 22 ] were consistent with what has been found in other studies [ 15 , 23 ]. Nonetheless, these two methodological weaknesses regarding the ascertainment of ED may lead to misclassification between incident ED and healthy controls.…”
Section: Resultssupporting
confidence: 86%
“…This imbalance of distribution is in accordance with previous findings that men with RLS have a higher risk for developing ED. Furthermore, the magnitude of that risk can also increase in combination with other sleep disorders such as OSA [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of interaction has not been clarified yet, but it may be because RLS and ED have similar biological processes, including autonomic dysfunction and dopamine deficiency. A 6-year prospective study found that RLS was a risk factor for developing ED with a relative risk of 1.33, and the frequency of RLS symptoms had a linear relationship with the magnitude of the that risk [112]. In a recent case-control study with 50 subjects each, Kurt [113] reported that not only ED but also premature ejaculation is more common in men with RLS than in controls.…”
Section: Main Bodymentioning
confidence: 99%